Spiritualisation of the Coronavirus in Africa: Comparative Analysis of Zimbabwe’s Prophet Emmanuel Makandiwa and Nigeria’s Prophet TB Joshua - Nenjerama, Theophilus Tinashe (Journal of religion in Africa, 2025)
The advent of the coronavirus pandemic shook the globe. The prevalence of the pandemic was interpreted differently in different quarters. African religious leaders also interpreted the pandemic spiritually. In the beginning of the pandemic the prophets reiterated their past prophecies about the disease from the sea that would rock the world. For many contemporary prophets the emergence of this disease was a confirmation of prophecy. This paper assesses the ways in which coronavirus has been spiritualised. In so doing it underscores the inextricable nexus between disease and religion. The study uses the case of the Nigerian prophet TB Joshua and the Zimbabwean prophet Emmanuel Makandiwa, and critically engages with the myriad ways by which coronavirus was interpreted through a spiritual lens by both. Where relevant, the study compares their prophecies. The article argues that some of the theologies behind the interpretation call for a close analysis in terms of their impact on the community of the followers of both Joshua and Makandiwa. Critical Discourse Analysis is used to analyse the prophesies of these two prophets about the virus during the pandemic.